Peningkatan Edukasi Pengetahuan UMKM Bakpia Pathok 731 Dewa Dalam Identifikasi Ancaman dan Pengendalian Siklus Bisnis - Wardhani, Aurelia Melinda Nisita (Universitas Negeri Padang, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a type of business that contributes to the economy in Indonesia. This knowledge-increasing educational activity is important to do in order to add insight into the importance of the role of internal control in the income cycle at UMKM